2021
DOI: 10.26508/lsa.202000774
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the micro-proteome of the nuclear lamina and lamina-associated domains

Abstract: The nuclear lamina is a proteinaceous network of filaments that provide both structural and gene regulatory functions by tethering proteins and large domains of DNA, the so-called lamina-associated domains (LADs), to the periphery of the nucleus. LADs are a large fraction of the mammalian genome that are repressed, in part, by their association to the nuclear periphery. The genesis and maintenance of LADs is poorly understood as are the proteins that participate in these functions. In an effort to identify pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 120 publications
0
33
0
1
Order By: Relevance
“…GO-analyses were performed using Clusterprofiler v4.0.0 31 . For GO-based comparison of ProtA-Turbo Emerin with other published lamin-targeting strategies, we used data for nuclear lamina microdomain mapping (LAP2B-BioID 32 ), a two-component lamina BioID mapping strategy (2C-BioID 33 ), conventional Lamin A BioID 3 , and an antibody-HRP-based method for biotinylation by antibody recognition (BAR 17 ). Enriched proteins were defined according to the following criteria: LAP2B-BioID > 1.5-FC/ctrl; 2C-BioID > 1.5-FC/ctrl (-noAP21967); Lamin A BioID: proteins were downloaded from Table S1 ; BAR: all proteins of the LMNA Unbound sample that are >2 fold enriched over control, were not shared with the no antibody control and had at least 2 unique peptides.…”
Section: Methodsmentioning
confidence: 99%
“…GO-analyses were performed using Clusterprofiler v4.0.0 31 . For GO-based comparison of ProtA-Turbo Emerin with other published lamin-targeting strategies, we used data for nuclear lamina microdomain mapping (LAP2B-BioID 32 ), a two-component lamina BioID mapping strategy (2C-BioID 33 ), conventional Lamin A BioID 3 , and an antibody-HRP-based method for biotinylation by antibody recognition (BAR 17 ). Enriched proteins were defined according to the following criteria: LAP2B-BioID > 1.5-FC/ctrl; 2C-BioID > 1.5-FC/ctrl (-noAP21967); Lamin A BioID: proteins were downloaded from Table S1 ; BAR: all proteins of the LMNA Unbound sample that are >2 fold enriched over control, were not shared with the no antibody control and had at least 2 unique peptides.…”
Section: Methodsmentioning
confidence: 99%
“…Given that the lamin meshwork forms a scaffold for the attachment of genomic DNA packaged into chromatin, it is possible that substitutions at R264 disrupt such contacts [19,[23][24][25]. To test for this, we analyzed the degree to which the fluorescent DAPI signal colocalized with the fluorescent signal from antibodies to LamC and lamDm 0 using the JACoP plugin for Fiji [68,69].…”
Section: Larval Body Wall Muscle-specific Expression Of R264q and R264w Did Not Affect Motility But Caused Pupal Lethalitymentioning
confidence: 99%
“…Support for this statement comes from studies showing that transient nuclear rupture and increased DNA damage are observed in skeletal muscle nuclei, which experience mechanical stress [21,22]. Lamins provide a scaffold for attachment of chromatin to the nuclear envelope at specific genomic locations called lamin-associated domains (LADs), which play a role in the orchestration of proper gene expression [19,[23][24][25]. LADs attract specific non-histone chromosomal proteins and are enriched for histone H3K9 tri-methylation, an epigenetic gene silencing mark [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations